Pregnant women’s perception concerning partners’ absence during pre-natal care - Silva, Flávio César Bezerra da; Brito, Rosineide Santana de (Rev Rene, 2010)
This study describes pregnants’s perception about partner’s conducts concerning his absence in prenatal care. This is a descriptive exploratory research with qualitative approach which had as a methodological referential the based theory and simbolic interactionism. The investigation occurred with 20 pregnant women enrolled in the program of prenatal care in a primary care unit of a small town in Natal-RN, Brazil in 2009. The results indicate that pregnant women perceive the partner’s interest for pregnancy when they show concern for her and the fetus. However, they acknowledge that he sometimes devalues her complaints, which predisposes to conflicts and marital disharmony. So, they admit to live with positive and negative attitudes towards the partner. This reality requires implementation of measures to encourage the involvement of the partner in this context.